Potential use of new cooling technologies during Tokyo 2020 Olympics and associated ethical dilemmas - Muniz-Pardos, B.; Angeloudis, K.; Guppy, F. M.; Tanisawa, K.; Hosokawa, Y.; Ash, G.; Schobersberger, W.; Grundstein, A.; Bargoria, V.; Lwande, G. O.; Ombaka, J. H.; Ergen, E.; et al. (British Journal of Sports Medicine, 2021)
The environmental conditions during Tokyo Summer Olympics are expected to be comparable to previous years with air temperatures and relative humidity in excess of 30°C and >70%, respectively. A previous consensus statement highlighted the main considerations for prevention, recognition and treatment of exertional heat illnesses, while the impact of extreme heat on athletic performance is examined elsewhere. Cooling strategies applied before and during the exercise in the heat have been shown to help athletes better maintain their performances by lowering body heat storage and core body temperature. The Tokyo Games have also encouraged the development of wearable technologies that could also be used for prevention, diagnosis and real-time monitoring of skin and core temperature and will be trialled during competition in Tokyo 2020. Here, we aim to highlight the potential application of current novel technologies and the associated ethical dilemmas regarding their effectiveness, the use of athlete biodata and predictive algorithms.